Radiation doses from computed tomography practice in Johor Bahru, Malaysia. (April 2016) - Karim, M.K.A.; Hashim, S.; Bradley, D.A; Bakar, K.A.; Haron, M.R.; Kayun, Z.
Abstract: Radiation doses for Computed Tomography (CT) procedures have been reported, encompassing a total of 376 CT examinations conducted in one oncology centre (Hospital Sultan Ismail) and three diagnostic imaging departments (Hospital Sultanah Aminah, Hospital Permai and Hospital Sultan Ismail) at Johor hospital's. In each case, dose evaluations were supported by data from patient questionnaires. Each CT examination and radiation doses were verified using the CT EXPO (Ver. 2.3.1, Germany) simulation software. Results are presented in terms of the weighted computed tomography dose index (CTDIw ), dose length product (DLP) and effective dose ( E ). The mean values of CTDIw, DLP and E were ranged between 7.6±0.1 to 64.8±16.5 mGy, 170.2±79.2 to 943.3±202.3 mGy cm and 1.6±0.7 to 11.2±6.5 mSv, respectively. Optimization techniques in CT are suggested to remain necessary, with well-trained radiology personnel remaining at the forefront of such efforts. Highlights: We investigate radiation doses received by patients from CT scan examinations. We compare data with current national diagnostic reference levels and other references. Radiation doses from CT were influenced by CT parameter, scanning techniques and patient characteristics.